IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA BERBASIS TEKNOLOGI INFORMASI UNTUK PENINGKATAN PENJUALAN - Ratnawati, Margareta; H. Nuryanto; Dasmadi, Dasmadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Increasing sales in today's business world requires a sophisticated and efficient approach to human resource management. Information technology has played a key role in the transformation of the way companies manage their human resources. This research presents the concept of implementing information technology-based human resource management to increase sales. The implementation of information technology, such as human resource management systems (HRMS), data analytics, and collaboration platforms, can make it easier for companies to monitor, manage, and optimize their workforce. This can result in increased productivity, employee motivation, and ultimately, increased sales. This research discusses various aspects of implementation, such as selecting and integrating appropriate technology, employee training, and expected benefits. The research results show that the implementation of information technology-based human resource management has been able to transform companies into entities that are more adaptive and responsive to market changes. Thus, companies can increase their sales significantly. This study will also include several successful case examples from companies that have implemented this concept, thereby providing practical guidance for other organizations wishing to adopt a similar approach. This research supports the idea that information technology has great potential to improve human resource performance and then increase company sales. As a result, companies need to consider implementation strategies that suit their goals and needs to maximize results.